ROS 2018
DOI: 10.20455/ros.2018.855
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots Protect against Copper Redox-Mediated Free Radical Generation and Cardiac Cell Injury

Abstract: In this work, we investigated the effects of graphene quantum dots (GQDs) on copper redox-mediated free radical generation and cell injury. Using electron paramagnetic resonance (EPR) spectrometry in conjunction with 5,5-dimethyl-1-pyrroline N-oxide (DMPO) as a spin trap, we found that GQDs at a concentration as low as 1 μg/ml significantly inhibited Cu(II)/H2O2-mediated hydroxyl radical formation. GQDs also blocked Cu(II)-catalyzed nucleophilic addition of H2O to DMPO to form a DMPO-OH adduct in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We recently showed that GQDs could potently block the Cu(II)/Cu(I) redox cycle likely via sequestering the copper ions, thereby preventing them from participating in the redox reactions [6]. Accordingly, inhibition of the Cu(II)/Cu(I) redox cycle may be primarily responsible for the protective effects of GQDs on oxidative DNA damage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that GQDs could potently block the Cu(II)/Cu(I) redox cycle likely via sequestering the copper ions, thereby preventing them from participating in the redox reactions [6]. Accordingly, inhibition of the Cu(II)/Cu(I) redox cycle may be primarily responsible for the protective effects of GQDs on oxidative DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…The EPR sample reactions were carried out in 0.1 ml DpBS, and the samples were loaded into 50-μl capillary tubes (Drummond Scientific, Broomall, PA, USA) before subjecting to the ERP measurement [6]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, GQDs were tested for their ability to scavenge free radicals in vitro in cardiomyocytes. It was found that GQDs at a concentration of 1 μg/ml were able to protect cardiomyocytes from H 2 O 2 -mediated cell injury [ 185 ].…”
Section: Application Of Cnms In Cardiovascular Tissue Engineeringmentioning
confidence: 99%